Designing Digital Scratch Media with Multiliteracy Strengthening Based: How to Improve Early Reading Skills? - Komala, Komala; Mubiar, Mubiar; Isah, Isah (International Journal of Research in Counseling and Education, 2024)
The design of digital scratch media with multiliteracy reinforcement based on local wisdom is very important to be developed to improve early reading skills in elementary schools. This is important to do because the learning media used by teachers in early reading learning are not all interactive. The purpose of this study was to determine the effectiveness of designing digital scratch media to improve early reading skills in elementary schools. The method used in this study is Thiagarajan's Four-D with four stages, namely: Define, Design, Develop, Disseminate. The research area is Padalarang District, West Bandung Regency, West Java Province, Indonesia. Elementary schools in the area consist of 5 schools with the subjects of this study being first grade students. Data collection techniques were carried out by interviews, documentation studies, observations and tests. Data analysis techniques used with qualitative approaches (data reduction, data display, drawing conclusions and triangulation) and quantitative (t-test). The results of the study showed that the early reading ability of the group of students who learned using local wisdom-based Scratch media had a better average score compared to the early reading ability of the group of students who learned without using Scratch media. This shows that the design of Scratch media can help students to motivate students at the beginning of reading starting from pronunciation, intonation, fluency, clarity and completeness of reading. The design of Scratch digital media makes it easy for teachers to design learning steps, arrange interactive materials and media for early reading learning.